DSW Solutions Sdn Bhd - Challenges for a Small & Medium Size Enterprise (SME) it Company in the Malaysian Environment - Yusof, Mohar (1998)
The formation of DSW Solutions Sdn Bhd came into being because the joint venture project that Haji Yusof and Mat Zahari had tried to work on failed to materialise. In 1993, while he was still attached to ICL Computers, Mat Zahari was approached by his ex-Commercial Director in Siemens Nixdorf, Mr. Freddy De Becker, to assist Mr. De Becker in finding a local partner to enable the formation of a local set-up for Siemens to penetrate the government sector market.Mat Zabari resorted to Haji Yusof for the search of the local partner. It took them more than two years to initiate an arrangement. Finally, after so many discussions, late nights, a few interested companies and various ways to initiate the start-up, a local company known as Mekar Idaman Sdn Bhd led by Dr. Azman Firdaus Shafii, verbally agreed to be the local investor with a 60% shareholding in the joint venture company. Siemens AG of Germany, the parent company of Siemens Nixdorf (M) Sdn Bhd would hold 30% while the balance would be reserved to Haji Yusof, Mat Zahari and the pioneer staffs of the joint venture company. Mr. De Becker had manoeuvred for Siemens AG to be involved because he did not see eye to eye on so many things with the Managing Director of Siemen Nixdorf (M) Sdn Bhd, Mr. Rolf Magruer, whom he perceived not to be a straight fellow. Siemens practised the matrix system. So, Mr. Rolf Magruer and Mr De Becker report to different bosses in Siemens AG.